Gen Z: Obstacles, Ease and Strategies for Implementing the Values of the Quran at Islamic State University: Gen Z: Hambatan, Kemudahan dan Strategi Penerapan Nilai-Nilai Al-Quran di Universitas Islam Negeri - Rahmah, Rafiqah Dwi; Ratnasari, Dwi; Mujahid, Mujahid (Institut Agama Islam Negeri Kerinci, 2023)
Nowadays, the productive age is dominated by Generation Z, which is an all-digital generation. Practicing the teachings of Islam in modern times with its ease is a problem for Generation Z. The discussion of this study reveals the obstacles, conveniences and strategies that Gen Z does in carrying out religious teachings. The discussion in this study reveals the obstacles, conveniences and strategies that Gen Z does in carrying out religious teachings. Therefore, the researcher made this study to find out the understanding of the religious values of generation Z and how to maintain the religious values of generation Z in the Qur'anic approach. The research method used is qualitative research which is critically described. Then using data collection techniques through semi-structured interview sessions while still making question guidelines. This research is a case study conducted on students of the Faculty of Science and Technology Physics Study Program at UIN Sunan Kalijaga Yogyakarta. The interviewees consisted of two Physics Study Program students. The data analysis technique in this study uses triangulation techniques so that the results of this study are richer with scientific treasures in it. The results of this study indicate that Generation Z's understanding of religious values is Iman, Islam, Ihsan, Taqwa and Tawakal. Then the way generation Z maintains its religious values by making commitments to themselves, choosing good friendships, maximizing existing resources as a medium to remind themselves, understanding how the world of social media works and managing emotions well. The efforts made in facing various obstacles, conveniences and strategies are a form of self-serving to Allah by making the Qur'an as a guide to life.